Deep Learning and Vision Transformer for Medical Image Analysis - Yudong Zhang; Jiaji Wang; Juan Manuel Gorriz; Shuihua Wang (Journal of Imaging, 2023)
Artificial intelligence (AI) refers to the field of computer science theory and technology [...]